E-LEARNING DAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Muchamad Suradji; Abdul Haris; Khozin Khozin (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
The purpose of this study is to find out to know e-learning and its implementation in learning. The type of research used by research is literature study or library research. The data sources in this study were obtained from books and scientific articles from the Garuda Portal, Google Scholar and Mendeley, according to the theory discussed, especially e-learning and its implementation in learning. The analysis technique used is descriptive analysis, which is to describe the sub-topic of research, then analyzed to get research conclusions. The results of research obtained from the study of e-learning and its implementation in learning that the development of the times and the needs of society are inevitable, including technological developments. Covid-19 has changed the paradigm of the world of education that e-learning can be an alternative choice of learning media. Some of the platforms used include Google Classroom, Google Form, Google Meet, Zoom Meet, and Whats App. E-learning can help the learning and teaching process of teachers and students. In addition, with this application students can learn independently and can study anywhere and anytime. Teachers can also provide materials and assignments to students without having to face-to-face with students and students can see their learning results directly through this e-learning application.